Solvothermal upcycling of spent LiFePO4 cathode materials into high-voltage LiMn0.5Fe0.5PO4 via a dual-olivine intermediate - Ye Hong; Fan Wang; Chunjiao Hu; Penghui Tan; Tianhua Shang; Heng Kuang; Lingchao Kong; Jin Li; Qianqian Hu; Jian Ouyang; Zilong Tang; Shuaibo Zeng (Journal of Environmental Chemical Engineering, 2026)

Dual-responsive injectable hydrogel loaded with DPSCs accelerates diabetic wound healing by promoting mitochondrial transfer to reduce senescent cells - Yonghao Liu; Pengcheng Pang; Shangjin Feng; Wanyang Zhong; Juan Wang; Ye Liu; Xiaoyu Zheng; Ziwei Li; Heng Zhou; Yan He; Qingsong Ye (Chemical Engineering Journal, 2026)

Overlooked dissemination risk of resistomes in mining soil environments - Li Tian; Jia-nan Lu; Yun Zhang; Qiqing Zhang; Gengbo Jiang; Yalin Yin; Liguan Li; Ying-heng Fei; Ying Yang; Zhepu Ruan; Yongjun Guo; Shizhong Wang; et al. (Journal of Hazardous Materials, 2026)

Click-crosslinked nano-hydrogel enables metabolic immune reprogramming for diabetic foot ulcers - Heng Gong; Tingjiang Gan; Xikun Ma; Ye Wu; Yaxing Li; Shijiu Yin; Biao Cao; Xiangtian Deng; Cheng Zheng; Yunbing Wang; Hui Zhang (Science China Life Sciences, 2026)

Reprogramming senescent granulosa cells for germ-cell generation - Dai Heng; Kairang Jin; Guoxing Yin; Chenglei Tian; Xiaoyan Sheng; Jiangtao Lu; Yiwei Wu; Xiaoying Ye; Panpan Shi; Huiyu Li; Chang Liu; Lin Liu; et al. (Science China Life Sciences, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Metabolomic and transcriptomic analysis reveals the impact of fruit bagging on cork spot disorder in ‘Akizuki’ pear fruit - Xueqian Wang; Lingxia Chen; Zixiao Wu; Jie Deng; Jintong Hu; Wei Wu; Bing Jia; Lun Liu; Xiaomei Tang; Li Liu; Zhenfeng Ye; Wei Heng (Postharvest Biology and Technology, 2026)

Hotspots & trends of lactic acid bacteria fermentation characteristics: A bibliometric analysis - Xudong Zhao; Kaiyue Wang; Xinqi Wang; Wei Liu; Jia Li; Zhaojun Ban; Xingqian Ye; Heng Xu; Xiaoyu Wang; Yimiti Baharrguli; Longying Pei; Xujie Hou (Food and Humanity, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

Grain yield and functional substance content in colored ratoon rice system under low solar radiation stress in southern China - Shaokun Song; Heng Zhang; Long Chen; Yixue Mu; Song Li; Ye Tao; Zaid Ulhassan; Haider Sultan; Lixiao Nie (Field Crops Research, 2025)

Cinnabar-dependent eye pigmentation mediates light input for circadian behavior synchronization in Spodoptera frugiperda - Zi-Jing Zheng; Shen-Lei Li; Shu-Ting Fan; Ze-Yuan Zhang; Shang-Huan Huang; Xi-Yu Ye; Guan-Heng Zhu (Journal of Insect Physiology, 2025)

A single N-rich covalent organic framework-based sensor for electrochemical sensing of 2,4,6-trichlorophenol - Wei-Long Shan; Qian Lu; Heng-Ye Li; Zhong-Xia Wang; Rui Zhang; Mei-Jie Wei; Fen-Ying Kong; Wei Wang (Food Chemistry, 2025)

Rapid and non-destructive detection of formaldehyde adulteration in shrimp based on deep learning-assisted portable Raman spectroscopy - Chencheng Wei; Jiheng Zhang; Gaozheng Li; Yi Zhong; Zhaoting Ye; Handong Wang; Kezhi Li; Yuanzi Wu; Yuezhong Wu; Heng Luo; Qi Sun; Zuquan Weng (Food Chemistry, 2025)

Morphology-engineered porous MgO for efficient CO2 capture and ciprofloxacin removal - Deyan Li; Heng Zhang; Guotao Xiao; Zhicheng Zhang; Wei Wang; Junwei Ye (Environmental Research, 2025)

Aquaculture types drive variability in mangrove soil carbon-nitrogen stocks and OC sources via dredging wastewater - Jiajia Wu; Liyue Liu; Hanyi Li; Jiahui Chen; Guangcheng Chen; Heng Zhu; Jun Liu; Yong Ye (Environmental Pollution, 2025)

Polystyrene/polylactic acid microplastics impair transzonal projections and oocyte maturation via gut microbiota-mediated lipoprotein lipase inhibition - Jiacheng Zhang; Hangqi Hu; Yutian Zhu; Xiyan Xin; Yuxin Jin; Qiancheng Zhao; Haolin Zhang; Dai Heng; Ze Ma; Xicheng Chai; Ruifan Lin; Yue Zhao; et al. (Journal of Hazardous Materials, 2025)

Chalcogen heteroatom engineering of non-halogenated volatile solid additives based on phthalic anhydride enables high-performance polymer solar cells - Tao Li; Yu Zhu; Xiujie Peng; Heng Li; Linglong Ye; Qingyuan Wang; Zhi-Guo Zhang; Ping Shen; Chao Weng (Chemical Engineering Journal, 2025)

Longitudinal relationships between changes in post-COVID mental fatigue and neuropsychiatric symptoms across distinct recovery trajectories - Wenrui Bao; Siyuan Chen; Ningkun Hong; Gengchen Ye; Chiyin Li; Jingmei Xie; Peng Li; Heng Li; Yang Wang; Jixin Liu; Xuan Niu; Yuchen Zhang (Inflammopharmacology, 2025)

Viral diversity and auxiliary metabolic genes in rare earth element mine drainage in South China - Chang Hu; Jia-nan Lu; Ziwu Chen; Li Tian; Yalin Yin; Gengbo Jiang; Ying-heng Fei; Ye-Tao Tang; Shizhong Wang; Chao Jin; Rongliang Qiu; Yuanqing Chao (Water Research, 2025)

Triphase photocatalytic hydrogel for molecule oxygen activation with enhanced interfacial electric field by Ti-O-Fe bridging bond - Litao Jia; Heng Ye; Xiangkang Zeng; Zhiquan Hu; Klaus Müllen; Fanghua Li (Journal of Hazardous Materials, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Optimal TBM Cutter Penetration and Spacing for Varying Rock Strengths: Field Tests and Numerical Modeling - Xiaokang Shao; Heng Li; Hongyang Qian; Yunhua Niu; Xuexian Zhu; Shoujie Ye (Geotechnical and Geological Engineering, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Monitoring the circumferential cracking of inner concrete core in prestressed concrete cylinder pipe during wire-wrapping using distributed optical fiber sensors - Shuai Liu; Yanlong Li; Ye Zhang; Minghui Ma; Wen Qiu; Lei She; Heng Zhou; Kangping Li; Kaiyu Sun (Tunnelling and Underground Space Technology, 2025)

PbSQE3 and PbSQE6 regulates the formation of triterpenoid compounds in the russet mutant of ‘Dangshansuli variety’ pear - Zhenfeng Ye; Daozhi Yao; Qi Liu; Lingxia Chen; Lindong Dou; Jinhui Yu; Jie Deng; Zixiao Wu; Li Cao; Li Liu; Wei Heng (Acta Physiologiae Plantarum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Ni transformation and hydrochar properties during hydrothermal carbonization of cellulose - Peng Zhao; Shijie Yu; Ye Shui Zhang; Heng Cheng; Xiaoxiao Yang; Qinghai Li; Yanguo Zhang; Hui Zhou (Fuel, 2025)

Global warming creates the adaptation tipping points of livestock exposure to cold and heat stress on the Qinghai-Tibetan plateau - Ning Zhan; Weihang Liu; Tao Ye; Yiqing Liu; Zitong Li; Heng Ma (Agricultural Systems, 2025)

Post-modification of covalent organic framework functionalized aminated carbon nanotubes with active site (Fe) for the sensitive detection of luteolin - Ze-Qi Wei; Wei-Long Shan; Lei Li; Heng-Ye Li; Rui Zhang; Juan-Juan Gao; Zhong-Xia Wang; Fen-Ying Kong; Mei-Jie Wei; Wei Wang (Food Chemistry, 2025)

Inspired by the tessellation of strawberry achenes on skin: Preparation of ZIF-67 derived multifunctional flame retardant through supramolecular assembly of cobalt alginate biopolymer in melamine-containing polyphosphazene skeleton - Qianlong Li; Yu Lei; Xue Bi; Yina Liu; Ye-Tang Pan; Wei Wang; Wenchao Zhang; Congling Shi; Guan Heng Yeoh (Chemical Engineering Journal, 2025)

Dual activation of soybean resistance against Phytophthora sojae by pectin lyase and degraded pectin oligosaccharides - Guangzheng Sun; Yeqiang Xia; Kuikui Li; Qinsheng Zhu; Feifei Ding; Hui Gu; Zhichao Zhang; Xinrui Li; Xuan Mi; Jun Chen; Ruoting Yao; Sicong Zhang; et al. (Science China Life Sciences, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Direct near-infrared laser ignition of CL-20 by introducing DATNBI as a bi-functional additive: Energetic photosensitizer and self-assembly stimulator - Ping Ye; Heng Ding; Bo Yang; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Intelligent circumferential deformation prediction of structures in PCCP-E with a large diameter under internal water overpressure based on prototype experiments and Inception-ResNet-LSTM - Ye Zhang; Simin Yuan; Yanlong Li; Heng Zhou; Kangping Li; Lifeng Wen (Engineering Structures, 2024)

Hexavalent Chromium Detoxification by Biochars: Influences of Organic and Inorganic Electron Donors - Zhuofeng Ye; Ying-heng Fei; Manzhi Li; Jieyang Guan; Zhenhong Huang; Zhenwei Tan; Tangfu Xiao (International Journal of Environmental Research, 2024)

Paleoenvironmental evolution and organic matter accumulation of the lower Cambrian Maidiping marine black shales in the intracratonic basin, western margin of Sichuan Basin, South China - Guodong Xia; Yuehao Ye; Shugen Liu; Heng Wang; Jinmin Song; Wei Sun; Bo Ran; Kun Jiao; Guoliang Xie; Bin Deng; Zhiwu Li; Yun Zeng (International Geology Review, 2024)

Confined-immigration enhances water resistance and weatherability of highly transparent coatings for cultural heritage preservation - Lin Chen; Heng Zhang; Shilei Zhu; Zhuangzhuang Li; Wenwen Yu; Fengbo Zhu; Ya Nan Ye; Qiang Zheng (Chemical Engineering Journal, 2024)

Ferrate(VI)-based synergistic oxidation processes (Fe(VI)-SOPs): Promoted reactive species production, micropollutant/microorganism elimination, and toxicity reduction - Jie-Yu Cao; Ye Du; Xin Dai; Tong Liu; Zhong-Juan Wang; Jie Li; Heng Zhang; Peng Zhou; Bo Lai (Chemical Engineering Journal, 2024)

Integrating metagenomic and isolation strategies revealed high contamination of pathogenies and resistome in market shrimps - Lianwei Ye; Zhiwei Zheng; Yaling Wang; Qiao Hu; Liang Zhong; Heng Heng; Zhihao Guo; Runsheng Li; Edward Wai Chi Chan; Sheng Chen (Science of The Total Environment, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

ECM1 promotes migration and invasion in endometriosis - Chen Zhang; Hongyan Cheng; Xue Ye; Heng Cui; Yi Li; Honglan Zhu; Xiaohong Chang (Reproductive Biology, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Prevalence and genetic basis of tetracycline resistance in Vibrio parahaemolyticus isolates recovered from food products in Shenzhen, China during 2013 to 2021 - Lianwei Ye; Zhiwei Zheng; Yating Xu; Chen Yang; Heng Heng; Fuyong Li; Edward Wai Chi Chan; Sheng Chen (Science of The Total Environment, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Molecular mechanisms that regulate the heat stress response in sea urchins (Strongylocentrotus intermedius) by comparative heat tolerance performance and whole-transcriptome RNA sequencing - Lingshu Han; Pengfei Hao; Wenpei Wang; Yanglei Wu; Shuchao Ruan; Chuang Gao; Wanrong Tian; Ye Tian; Xiaonan Li; Luo Wang; Weijie Zhang; Heng Wang; et al. (Science of The Total Environment, 2023)

Discovery of Michael reaction acceptors from the leaves of Ailanthus altissima by a modified tactic - Zhi-Kang Duan; Shan-Shan Guo; Li Ye; Zhi-Heng Gao; Dai Liu; Guo-Dong Yao; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Full-coverage mapping high-resolution atmospheric CO2 concentrations in China from 2015 to 2020: Spatiotemporal variations and coupled trends with particulate pollution - Qingqing He; Tong Ye; Xiuzhen Chen; Heng Dong; Weihang Wang; Youjia Liang; Yubiao Li (Journal of Cleaner Production, 2023)

Oxygen vacancies mediate the degradation of refractory organics in the interflow around a simple landfill: Based on Mg-Fe3O4/PMS system - Hengyi Liu; Lei Li; Heng Zhang; Jin Guo; Wenjie Ye; Guotao Liu; Xuya Peng (Journal of Environmental Chemical Engineering, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Enhanced purification of hospital wastewater by a novel ferrate(VI) flocs recycling process - Jie Li; Ye Du; En-Yu Zhao; Yanni Jiang; Zhongjuan Wang; Heng Zhang; Peng Zhou; ZhaoKun Xiong; Bo Lai (Chemical Engineering Journal, 2023)

Surface-active site engineering: Synergy of photo- and supermolecular catalysis in hydrogen transfer enables biomass upgrading and H2 evolution - Ye Meng; Yumei Jian; Jie Li; Hongguo Wu; Heng Zhang; Shunmugavel Saravanamurugan; Song Yang; Hu Li (Chemical Engineering Journal, 2023)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Delayed body development with reduced triglycerides levels in leptin transgenic pigs - Yubo Qing; Muhammad Ameen Jamal; Dejia Shi; Sumei Zhao; Kaixiang Xu; Deling Jiao; Heng Zhao; Honghui Li; Baoyu Jia; Haizhen Wang; Hong-Ye Zhao; Hong-Jiang Wei (Transgenic Research, 2022)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Genetic characterization of qSCN10 from an exotic soybean accession PI 567516C reveals a novel source conferring broad-spectrum resistance to soybean cyst nematode - Lijuan Zhou; Li Song; Yun Lian; Heng Ye; Mariola Usovsky; Jinrong Wan; Tri D. Vuong; Henry T. Nguyen (Theoretical and Applied Genetics, 2021)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

Characterization of Pseudomonas syringae pv. actinidiae Biovar 3 strain and cultivar tolerance to kiwifruit bacterial canker in China - Zhen-feng Ye; Peng-fei Wei; Shi-zhou Xue; Pu Liu; Bing Jia; Wei Heng; Li-wu Zhu (Journal of Plant Pathology, 2020)

Overexpression of the pear PbSPMS gene in Arabidopsis thaliana increases resistance to abiotic stress - Xianghong Jiang; Junyu Zhan; Qi Wang; Xinyi Wu; Xiaonan Chen; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu; Wei Heng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Development of a loop-mediated isothermal amplification method for the rapid detection of Pythium ultimum - Danyu Shen; Qingling Li; Jia Yu; Yuanyuan Zhao; Ye Zhu; Heng Xu; Daolong Dou (Australasian Plant Pathology, 2017)

Modelling the response of shallow groundwater levels to combined climate and water-diversion scenarios in Beijing-Tianjin-Hebei Plain, China - Xue Li; Si-Yuan Ye; Ai-Hua Wei; Peng-Peng Zhou; Li-Heng Wang (Hydrogeology Journal, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

The role of polyamines during exocarp formation in a russet mutant of ‘Dangshansuli’ pear (Pyrus bretschneideri Rehd.) - Wei Heng; Ziteng Wang; Xianghong Jiang; Bing Jia; Pu Liu; Li Liu; Zhenfeng Ye; Liwu Zhu (Plant Cell Reports, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Detection of Vulnerable Atherosclerotic Plaques in Experimental Atherosclerosis with the USPIO-Enhanced MRI - Chun-mei Qi; Lili Du; Wei-heng Wu; Dong-ye Li; Ji Hao; Lei Gong; Liangrong Deng; Tao Zhang; Chao Zhang; Yu Zhang (Cell Biochemistry and Biophysics, 2015)

Coumarin-containing aminophosphonates bridged with chiral side chain: synthesis and influence of chirality on cytotoxicity and DNA binding - Ya-Jun Li; Man-Yi Ye; Ri-Zhen Huang; Gui-Yang Yao; Ying-Ming Pan; Zhi-Xin Liao; Heng-Shan Wang (Medicinal Chemistry Research, 2014)

Differentially expressed genes related to the formation of russet fruit skin in a mutant of ‘Dangshansuli’ pear (Pyrus bretchnederi Rehd.) determined by suppression subtractive hybridization - Wei Heng; Li Liu; Meng-dong Wang; Bing Jia; Pu Liu; Zhen-feng Ye; Li-wu Zhu (Euphytica, 2014)

MicroRNA-98 induces an Alzheimer’s disease-like disturbance by targeting insulin-like growth factor 1 - Yi-Kui Hu; Xun Wang; Lian Li; Yan-Hua Du; Heng-Tai Ye; Cheng-Yan Li (Neuroscience Bulletin, 2013)

Genetic characterization of avian-origin H3N2 canine influenza viruses isolated from Guangdong during 2006–2012 - Heng Wang; Kun Jia; Wenbao Qi; Minze Zhang; Long Sun; Huanbin Liang; Guohao Du; Likai Tan; Zhenwen Shao; Jiahui Ye; Lingshuang Sun; Zhenpeng Cao; et al. (Virus Genes, 2013)

DEL RBC transfusion should be avoided in particular blood recipient in East Asia due to allosensitization and ineffectiveness - Chao-peng Shao; Bao-yan Wang; Shi-hui Ye; Wen-li Zhang; Hua Xu; Nai-bao Zhuang; Xiao-ying Wu; Heng-gui Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Floral development of Phyllanthus chekiangensis (Phyllanthaceae), with special reference to androecium and gynoecium - Zi-gang Zhang; Ai-ping Meng; Jian-qiang Li; Qi-gang Ye; Heng-chang Wang; Peter K. Endress (Plant Systematics and Evolution, 2012)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)